Clinical Characteristic of Different SARS-CoV-2 Variants in South Kalimantan, Indonesia: A Case Study - Haryati Haryati; Desi Rahmawaty; Mohamad Isa; Ali Assagaf; Ira Nurrasyidah; Erna Kusumawardhani (Althea Medical Journal, 2023)
Background: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has undergone various mutations of Corona Virus Disease 2019 (COVID-19). The World Health Organization (WHO) has designated B.1.617.2 (Delta) and B.1.1.529 (Omicron) as variants of concern (VOC). Since clinical features and epidemiological characteristics of patients infected with SARS-CoV-2 variants remain largely unknown, especially in Indonesia, this study aimed to identify the clinical characteristics of COVID-19 patients from South Kalimantan, Indonesia.Methods: Data from medical records of COVID-19 patients at Ulin General Hospital Banjarmasin from June 2021 to February 2022 were randomly extracted, containing demographic data, comorbidities, and laboratory data, as well as the type of virus. Results: In total, 32 patients were included, 9 were infected with delta, 14 with probable omicrons, and 9 with non-VOC. Patients in the probable Omicron group were significantly older than other groups (median age 64 years old, range 54–73 years; p=0.049), had hypertension as the dominant comorbidity (85.7%; p=0.039), the onset appeared slightly earlier (median 3 days; range 2-3 days, p=0.062), with no anosmia symptom (p=0.006). Critical illness predominated and mostly survived in all variants but was not statistically significant (p=0.590 and 0.726, respectively). The three variants showed similarities in laboratory findings; hence, statistical analysis suggested that the leucocytes differed significantly (p=0.020).Conclusions: Patients with the likely Omicron variant are much older, have hypertension as their main comorbidity, do not have any symptoms of anosmia, and have higher leukocyte counts compared to other variants.